Model of Resources Development in Partnership System of Broiler Farming Business - Amam Amam; Zaenal Fanani; Budi Hartono; Bambang Ali Nugroho (Jurnal Ilmu Ternak dan Veteriner, 2019)
Accessibility of resources in theory can affected the development of broiler farming in a region. This research was conducted with the objectives of: 1) to formulate indicators of resource use on the development of partnership system of broiler farming business, and 2) to find the model of the development of resources use accessibility to partnership system of broiler farming business. The research was conducted in August 2017 up to January 2018 in Malang Regency of East Java Province, Indonesia. 100 respondents as partnership system of broiler farmer was participated in this study who was determined by total sampling. The research variables consist of: a) financial resources, b) technology resources, c) physic resources, d) economic resources, e) environmental resources, f) social resources, g) human resources, and h ) business development. The data was analyze used by SEM with SmartPLS 2.0 analysis tool. The results indicate that: 1) The development of partnership system of broiler farming business is directly influenced by the financial resources of 2.421, the physic resources is 1.821, the economic resources 2.445, and the human resources 2.904, but the development of partnership system of broiler farming business direct are not affected by technology resources, environmental resources, and social resources; 2) The development of partnership system of broiler farming business is indirect with quality of human resources is influenced by the financial resources of 2.629, technology resources of 6.092, physic resources of 2.308, and economic resources of 2.312, but the development of partnership system of broiler business is indirectly with the quality of human resources are not influenced by environmental resources and social resources.